2013
DOI: 10.5139/ijass.2013.14.3.272
|View full text |Cite
|
Sign up to set email alerts
|

A Development of 3-D Resolution Algorithm for Aircraft Collision Avoidance

Abstract: Traffic Collision Avoidance System (TCAS) is designed to enhance safety in aircraft operations, by reducing the incidences of mid-air collision between aircraft. The current version of TCAS provides only vertical resolution advisory to the pilots, if an aircraft's collision with another is predicted to be imminent, while efforts to include horizontal resolution advisory have been made, as well. This paper introduces a collision resolution algorithm, which includes both vertical and horizontal avoidance maneuve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The design of new navigation and guidance systems with improved accuracy for spatial and temporal trajectory tracking has turned possible free flight which has appeared as an appealing opportunity for airlines. However, in the case of high traffic density regions, the adoption of free flight should result, even through a 3D+T trajectory negotiation process with ATM, into an increasing number of conflicts which are solved by modifying these aircraft trajectories [1][2][3]. The development of fully automatic on-board conflict resolution devices will ease in some way the traffic control task but the resulting traffic will be in a permanent reconfiguration and its monitoring by ATC will become more and more difficult.…”
Section: Introductionmentioning
confidence: 97%
“…The design of new navigation and guidance systems with improved accuracy for spatial and temporal trajectory tracking has turned possible free flight which has appeared as an appealing opportunity for airlines. However, in the case of high traffic density regions, the adoption of free flight should result, even through a 3D+T trajectory negotiation process with ATM, into an increasing number of conflicts which are solved by modifying these aircraft trajectories [1][2][3]. The development of fully automatic on-board conflict resolution devices will ease in some way the traffic control task but the resulting traffic will be in a permanent reconfiguration and its monitoring by ATC will become more and more difficult.…”
Section: Introductionmentioning
confidence: 97%
“…Radar is an essential safety facility also used by aircraft and other systems. CPA is therefore not only useful for ship safety, but also helpful for aircraft collision avoidance (Kim et al, 2013) and vehicles (Huang and Lin, 2012). Pimontel (2007) looked at the factors that might affect CPA and suggested that there were no clear relationships between the vessel type and CPA, between the vessel dimension and CPA, or between the vessel speed and CPA.…”
Section: Introductionmentioning
confidence: 99%